2008
DOI: 10.1111/j.1469-0691.2008.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Cryptococcus gattii clinical isolates

Abstract: The data available in the literature concerning Cryptococcus gattii in vitro antifungal susceptibility are contradictory. We have analyzed the activity of eight antifungal agents against 23 C. gattii clinical isolates and compared the susceptibility profiles with those of C. neoformans. MIC analysis (mg/L) revealed that C. gattii isolates were more susceptible to amphotericin B and flucytosine than were C. neoformans isolates. Fluconazole and other azole compounds showed high MIC values for C. gattii. Posacona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 19 publications
5
36
2
5
Order By: Relevance
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…To our knowledge, this is the first study that explores the efficacy of these drugs in a murine C. gattii infection. In contrast to the high in vitro activities of PSC and VRC, which agree with the findings of other authors (13,29), these drugs showed lower efficacy than AMB in vivo against C. gattii. In this study, the high mortality of mice treated with VRC or PSC seems to be associated with the inability of these drugs to reduce the fungal load in the brain despite increased drug levels in the organ.…”
Section: Discussioncontrasting
confidence: 53%
“…This is corroborated by various in vitro studies that have found that C. gattii may be less susceptible than C. neoformans to antifungal agents, in particular, fluconazole (13,17,44); however, other studies report no significant differences in susceptibility (9,43). A possible reason for these contradictory findings is that most studies have not considered genetic or geographic differences within the two Cryptococcus species.…”
mentioning
confidence: 56%
“…While a number of studies have found C. gattii to be less susceptible than C. neoformans to azole drugs, particularly FLC (13,17,44), others have reported no difference between the two species (9,43). Data on susceptibility to AMB and 5FC are even more varied, with comparisons indicating that C. gattii is more resistant than (9), more susceptible than (17), or not different from (43, 44) C. neoformans.…”
Section: Discussionmentioning
confidence: 84%